Work Stress and Job Satisfaction among Police Officers at Palembang Resort Police Station - Choirul Alfan; Nuzsep Almigo (Hasanuddin University, 2024)
The aim of this research is to find out the relationship between work stress and job satisfaction among Indonesian National Police (Polri) officers at Polrestabes Palembang. Job satisfaction is the level of contentment or discontent an employee feels with their work, whereas work stress is the reaction a person has to demands that exceed their capability. The poll's Likert scale was used to measure how stressed and satisfied workers were with their jobs. For the sample, 155 officers of Polrestabes Palembang were selected through the technique of purposeful random selection. The Kolmogorov-Smirnov normality and linearity tests were used to validate the data. Using basic regression analysis, the result proved that there is a highly significant negative correlation (r = -0.933) between job stress and job satisfaction, with a significance level of p = 0.000 (p < 0.01). According to these results, 87% of the variance in job satisfaction may be attributed to job stress, with the remaining 13% being influenced by factors that are yet unclear. The results of the study demonstrate that among Palembang resort police station officers, higher job stress is substantially correlated with poorer job satisfaction, underscoring the need for management to address and mitigate stressors in order to improve job satisfaction.